2018
DOI: 10.24052/jbrmr/v12is03/art-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative advantages of Kazakhstan assessed by the Balassa Index: consistently competitive exports are limited to raw materials with low added value

Abstract: The aim of this study is to determine the competitive advantages of Kazakhstan in trading with other countries based on revealed comparative advantages, in which the interlinked commodity exchanges will be developed in the medium-term. This research applies the index of comparative advantages. The paper presents an empirical analysis of the competitive advantages of Kazakhstan export products. The Balassa Index was proposed for Kazakh six-digit HS product category level, the choice of which was due to their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…According to Ahrend (2004), it is particularly true for Russia between 1997-2003, where revealed comparative advantage was limited to some raw materials and energy-based products. It is the same for Kazakhstan, where only low value added raw materials showed comparative advantage, and agricultural and food industrial products showed weakening competitive position (Madiyarova et al, 2018). However, this sector still plays an important role in the CIS countries compared to the developed world.…”
Section: Introductionmentioning
confidence: 92%
“…According to Ahrend (2004), it is particularly true for Russia between 1997-2003, where revealed comparative advantage was limited to some raw materials and energy-based products. It is the same for Kazakhstan, where only low value added raw materials showed comparative advantage, and agricultural and food industrial products showed weakening competitive position (Madiyarova et al, 2018). However, this sector still plays an important role in the CIS countries compared to the developed world.…”
Section: Introductionmentioning
confidence: 92%
“…The RC consists of logarithmic forms of the RXA and RMA. A positive value obtained for the RC shows that there is a competitive advantage, and a negative value shows that there is a competitive disadvantage (Fertö and Hubbard 2003, Sarıçoban and Kösekahyaoğlu 2017, Madiyarova et al 2018). The equation of RC is the following:…”
Section: Revealed Competitiveness (Rc)mentioning
confidence: 99%
“…The most benefiting sectors from the accession in Kazakhstan are the metallurgy, transport, chemical, and consumer goods industry (Amirbekova et al, 2017). The agricultural sector and auto industry go through some challenges as the former will start to receive less government subsidy, and the latter's import tariff will be declined significantly -from 27.9% to 13.3% (Onyusheva and Nizamova, 2015).…”
Section: Domestic Debates On Kazakhstan's Wto Accessionmentioning
confidence: 99%